Arsitektur Masjid Jami' “Sunan Dalem” Gresik Tahun 1500-2000 - Novi Dwi Andriani; Imam Ibnu Hajar (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
Abstract: The article entitled